A House of Worship for Every Religious Community: The History of a Mālikī Fatwā - Safran, Janina M. (Islamic law and society, 2023)
This essay traces the incorporation of a sixth/twelfth century fatwā supporting the construction of churches in North Africa in the Mālikī madhhab and provides insight into practices of Mālikī legal interpretation in the Maghrib in the ninth/fifteenth century. In his fatwā, the Cordoban jurist Ibn al-Ḥājj (d. 529/1134) addressed a novel situation involving the relocation of Christians from al-Andalus. This fatwā was selected by the Tunisian jurist al-Burzulī (d. 841/1438) for commentary in his Jāmiʿ masāʾil al-aḥkām. He discussed Ibn al-Ḥājj’s opinions with reference to al-Mudawwana and al-Wāḍiḥa, and later commentaries, and made a connection to church building in Tunis. In the late ninth/fifteenth century, three jurists writing in response to anti-Jewish attacks in Tamanṭīṭ, in the Tuwāt oasis (Algeria), cited Ibn al-Ḥājj’s fatwā, as redacted by al-Burzulī, in their opinions on the destruction of a local synagogue. Each jurist treated Ibn al-Ḥājj’s fatwā as a relevant legal precedent. At the same time, each reevaluated the parameters of Mālikī debate about non-Muslim houses of worship to assert his distinct opinion about the synagogue of Tamanṭīṭ and the position of the Mālikī madhhab on non-Muslim houses of worship in Muslim lands.